Challenges and Opportunities of Computer-Based Learning for Senior Citizens - Zaphiris, Panayiotis; Kurniawan, Sri Hastuti (My University, 2005)
This entry starts with an argument on how computer-based learning (CBL) can benefit senior citizens, then reviews the effects of aging on CBL. It finally discusses how the CBL material should be designed for senior citizens to facilitate their learning experience.